Analogical Reasoning in Geometric Problem Solving: A Cognitive Analysis Based on Sternberg’s Thinking Styles - Mulyani, Eva; Jailani, Jailani; Hartono, Hartono (International Journal of Geometry Research and Inventions in Education, 2024)
Analogical reasoning plays a vital role in mathematics learning, especially in helping students solve new problems by using structural similarities with known problems. Each student has a different thinking style, which influences how they process information to solve mathematical problems. This research aims to analyze the analogical reasoning thinking process in solving mathematical problems from the perspective of Sternberg's thinking styles. The study employs a qualitative approach with exploratory methods. This study involved 9th-grade students from a public junior high school in Tasikmalaya City, West Java. The results conclude that the complete and accurate analogical reasoning thinking process in solving mathematical problems is exhibited by the legislative, executive, judicial, local, and internal thinking styles.